The Kirwan Years - Perry, Chris (Book collections on Project MUSE., 2014)
Starting under President Edward Jennings and continuing under Gordon Gee, The Ohio State University began a long-term drive to match the school's ranking in football with a commensurate reputation for academic excellence. Initiatives to admit better-prepared students, attract and retain world-class faculty, and build highly rated programs were promising, but the university needed a broad strategy to coordinate these and other initiatives into a focused approach. Enter President William "Brit" Kirwan, who understood this need perfectly and whose major legacy became widely known as the Academic Plan. This document became and remains the centerpiece of Ohio State's agenda, with budget and other priorities emanating from its six strategies and 14 initiatives. Continuing the Ohio State tradition of chronicling the university's history through the work of its past presidents, The Kirwan Years recounts the Academic Plan's creation, acceptance, and initial implementation, along with many major university accomplishments from mid-1998 through mid-2002. It also details the university's ongoing, uphill struggle to maximize state financial support and its success in private and other fundraising. It provides a compelling look at the complexity permeating today's research universities. And yes, it describes the firing of football coach John Cooper and the hiring of Jim Tressel.